Policy and strategies addressing prevention and control of antimicrobial resistance in Brazil: A scoping review protocol. - Joslaine de Oliveira Nunes; Raissa Allan Santos Domingues; Roberto Mauro Pinto Coelho Barcellos; Bárbara Manuella Cardoso Sodré Alves; Isis Polianna Silva Ferreira de Carvalho; Noemia Urruth Leão Tavares (PLoS ONE)
Introduction Antimicrobial resistance (AMR) is considered one of the biggest health challenges of the 21st century. It has both social and economic consequences; therefore, timely review of public health policies that have been designed to manage AMR is essential. Brazil too has developed and implemented various polices for the prevention and control of AMR. However, till date, no study provides insights regarding the various public health policies or other programs implemented by Brazilian institutes. Objective The objective is to define a scoping review protocol of policies that were developed to address prevention and control of antimicrobial resistance in Brazil, from a human health perspective. Method This protocol has been registered in the Open Science Framework (DOI 10.17605/OSF.IO/EC9ZJ). Indexed literature in English, Spanish and Portuguese published till December 2020 in Lilacs, PubMed, Embase, and official websites of the Brazilian government will be reviewed. This review considers all studies identified through a comprehensive search of peer-reviewed and grey literature databases that have a reference for policies made for managing AMR in Brazil. The criteria for the scoping review will be set by two evaluators. A third evaluator will be consulted, if there is any disagreement between the two primary evaluators. A standardized form will be used for data extraction from the selected studies. The results will be presented in a tabular form with narrative abstracts related to the topics identified through the scoping review protocol. The PRISMA extension for Scoping Reviews tool will be used.